NUS: le monde gagne à manger local, Niger - Borelli, Teresa; Grazioli, Francesca; Falcis, Eleonora de; Naino Jika, Abdel Kader; Otieno, Gloria Atieno (2022)
Within the EU-funded SUSTLIVES project, this easy to read poster provides information on target neglected and underutilized species in Niger as well as information on their importance for nutrition, climate resilience and livelihoods.